Pre-service and In-service Teachers’ Metacognitive Knowledge of Learning Strategies - Halamish, Vered (Frontiers in Psychology, 2018)
Research in cognitive psychology has suggested that difficulties are often desirable for learning: learning strategies that create difficulties for learners during practice often produce durable learning. Prominent examples of effective learning strategies that introduce desirable difficulties are testing as a means of learning, spacing study sessions over time, and interleaving practice of different topics. Previous research has suggested that, generally, undergraduates' metacognitive knowledge about the effectiveness of these learning strategies is inaccurate. The goal of the current study was to extend the examination of metacognitive knowledge of learning strategies to pre-service and in-service teachers, and further examine whether teachers’ metacognitive knowledge is related to their teaching experience. Pre-service teachers enrolled in a university teacher training program (N = 83) and in-service elementary, junior-high, and high school teachers (N = 82) were presented with learning scenarios and predicted which of two learning strategies would yield the better outcome. Results suggested that, overall, both pre-service and in-service teachers failed to predict the advantages of testing, spacing, and interleaving as learning strategies. Furthermore, their knowledge of learning strategies failed to increase with teaching experience. It is, therefore, recommended that explicit instruction about the benefits of empirically supported learning strategies should be included in teacher training and development programs.